„Filozofia – dziełem Hellenów”. Prolog Diogenesa Laertiosa - Wesoły, Marian A. (Collectanea Philologica, 2023)
I dedicate this distich, together with the article, to Professor Zbigniew Danek. Indeed, there is probably no more comprehensive and fascinating work of ancient literature than Diogenes Laertios’ Lives and Views of Eminent Philosophers, the Prologue of which I present below in a new Polish translation. This Prologue is particularly interesting and instructive for understanding the composition and interpretation of the work, as in it the author gives his own criteria and distinctions of currents and branches of philosophy, whose origin, name and tradition is according to him typically Hellenic. In our translation, appropriate title headings have been introduced for greater clarity in the reading.